The micro and macro economics of short-time work - Pierre Cahuc (Rockwool Foundation Berlin (RF Berlin) and Centre for Research & Analysis of Migration (CReAM), 2024)
This article provides an overview of the economic literature on short-time work. It presents the main characteristics of short-time work since its emergence in Germany in the 1930s. It analyzes its effectiveness as a job preservation mechanism, drawing on theoretical models and empirical studies. It concludes by highlighting the areas that future research could explore to address the most significant gaps in our understanding of short-time work.
Keywords: J23; J41; J63; 330; Short-time work; furlough; employment; working hours